Online education : foundations, planning, and pedagogy - Picciano, Anthony G. (Routledge, 2019)
Online Education is a comprehensive exploration of blended and fully online teaching platforms, addressing history, theory, research, planning, and practice. As colleges, universities, and schools around the world adopt large-scale technologies and traditional class models shift into seamless, digitally interactive environments, critical insights are needed into the implications for administration and pedagogy. Written by a major contributor to the field, this book contextualizes online education in the past and present before analyzing its fundamental changes to instruction, program integration, social interaction, content construction, networked media, policy, and more. A provocative concluding chapter speculates on the future of education as the sector becomes increasingly dependent on learning technologies.